Mucilicious methods: Navigating the tools developed to Arabidopsis Seed Coat Mucilage analysis - Susana Saez-Aguayo; Dayan Sanhueza; Vicente Jara; Benjamin Galleguillos; Alfonso Gonzalo de la Rubia; Asier Largo-Gosens; Adrian Moreno (The Cell Surface)
During the last decades, Arabidopsis seed mucilage has been extensively studied to gain insight into the metabolism of pectin, hemicellulose and cellulose. This review aims to provide a comprehensive examination of the techniques used to understand the composition and structure of Arabidopsis mucilage. Moreover, we present novel findings from mucilage analysis, including the separation of pectic domains within the mucilage, offering a fresh perspective on utilizing traditional techniques to analyze mucilage mutant lines.